Diseño de un Embalse con fines de riego, para una finca en el sector Yambananga, de la parroquia Purunuma, del Cantón Gonzanamá, de la provincia de Loja - Alvarez Lino, Wilfrido Manuel (2022)
The availability of water is often the most limiting factor for agricultural production, as it is required in large quantities for the proper development of crops, in the same way, the reserves of water resources in the microbasins are limited, this because of the constant deterioration due to overexploitation of natural resources, as well as global warming has caused the water demand of crops to increase significantly. The research work was developed from September 2019 to February 2021, in the micro-watershed of the Yambananga stream, in the Purunuma parish; to determine precipitation, the meteorological stations surrounding the study area (Gonzanamá, Catamayo, Nambacola and Malacatos) were selected; based on the pluviometric data, the runoff in the stream was determined using the runoff coefficient method; ETo was determined with the Penman Montheith method, using the Cropwat 8. 0; two methods were used to calculate the useful volume of the reservoir (peak succession algorithm method and inverse mass curve method). The results show that the sector is differentiated by two periods; the first one with high water availability due to rainfall and the second one with water scarcity; water demand for crops increases in the last months of the year coinciding with the period of water scarcity. It is concluded that water should be stored during the months of precipitation in order to irrigate crops during the water shortage. It is recommended to carry out studies on the storage and use of water resources, which will allow crops to be grown for a longer period of time, guaranteeing agricultural production in the sector. Keywords: water resources, precipitation, water demand, ETo.